Short Notices (Reviews in religion and theology, 2004)
Shamanism: A Reader, Graham Harvey (ed.), Routledge 2003 (0-415-25330-6), pp. 461, Pb £17.99 Ancient Jewish Novels: An Anthology, edited and translated by Lawrence M. Wills, Oxford University Press 2002 (Hb 0-19-515141-0; Pb 0-19-515142-9), pp. x + 298, Hb £40.50, Pb £20 4QPesher Nahum: A Critical Commentary, Gregory L. Doudna, Sheffield Academic Press 2001, Journal for the Study of the Pseudepigrapha Supplement Series 35, Copenhagen International Series 8 (1-84127-156-X), pp. 813, Hb £95 Copper Scroll Studies, George J. Brooke and Philip R. Davies (eds), Journal for the Study of the Pseudepigrapha Supplement Series 40, Sheffield Academic Press 2003, A Continuum Imprint (0-8264-6055-0), pp. xvi + 344, Hb £95 Jesus in his Jewish Context, Geza Vermes, SCM Press 2003 (0-334-02915-5), pp. x + 198, Pb £12.99 The New Testament: History, Literature, Religion, Gerd Theissen, T. & T. Clark 2003, A Continuum Imprint (Hb 0-567-08948-7, Pb, 0-567-08949-5), pp. xii + 206, Hb £40, Pb £12.99 Mary Magdalene: Beyond the Myth, Esther de Boer, Translated by John Bowden, SCM Press 2003 (0-334-02690-3) pp. xi + 147, Pb £12.99 Slave of All: The Paradox of Authority and Servanthood in the Gospel of Mark, Narry F. Santos, JSNTS Series 237, Sheffield Academic Press 2003, A Continuum Imprint (0-8264-62251), pp. xii + 337, Hb £65 An Introduction to the New Testament Apocrypha, Fred Lapham, T. & T. Clark 2003, A Continuum Imprint (Hb 0-8264-6978-7, Pb 0-8264-6979-5), pp. ix + 193, Hb £70, Pb £14.99 The Spirit of Early Christian Thought: Seeking the Face of God. Robert Louis Wilken, Yale University Press 2003 (0-300-09708-5), pp. xxii + 368, Pb £22.50 Communication and the Gospel, John Holdsworth, Darton, Longman & Todd 2003 (0-232-52488-2), pp. xii + 119, Pb £8.95 From Angels to Aliens: Teenagers, the Media, and the Supernatural, Lynn Schofield Clark, Oxford University Press 2003 (0-19-515609-9), pp. xii + 292, Hb £20 Mediating Religion: Conversations in Media, Religion and Culture, Jolyon Mitchell and Sophia Marriage (eds), T. & T. Clark 2003, A Continuum Imprint (0-567-08807-3), pp. xv + 407, Pb £17.99 Introducing Christianity, Sally Bruyneel and Alan G. Padgett, Orbis Books 2003 (1-57075-395-4), pp. xi + 164, Pb $18 Problems in Theology 1, Creation: A Reader, Jeff Astley, David Brown and Ann Loades (eds), T. & T. Clark International 2003, A Continuum Imprint (0-567-08977-0), pp. vii + 119, Pb £12.99 Problems in Theology 2, Evil: A Reader, Jeff Astley, David Brown and Ann Loades (eds), T. & T. Clark International 2003, A Continuum Imprint (0-567-08975-0), pp. viii + 112, Pb £12.99 The Cambridge Companion to Postmodern Theology, Kevin Vanhoozer (ed.), Cambridge University Press 2003 (0-231-12733-2), pp. xv + 295, Pb £15.95/$23 Apostolicity and Unity: Essays on the Porvoo Common Statement, Ola Tjørhom (ed.), Eerdmans 2003 (2-8254-1375-5), pp. xii + 271, Pb £18.90/$30 Signs amid the Rubble: The Purposes of God in Human History, Lesslie Newbigin, Eerdmans 2003 (0-8028-0989-9), pp. xiv + 121, Pb £10.99/$15 The Ecclesiology of Stanley Hauerwas: A Christian Theology of Liberation, John B. Thomson, Ashgate New Critical Thinking in Religion, Ashgate 2003 (0-7546-3394-2), pp. x + 245, Hb £49.50 The Resurrection of God Incarnate, Richard Swinburne, Oxford University Press 2003 (Hb 0-19-925745-0, Pb 0-19-925746-9), pp. vi + 224, Hb £45, Pb £16.99 Truth in the Making: Creative Knowledge in Theology and Philosophy, Robert Miner, Routledge 2004 (0-415-27698-5), pp. xvi + 166, £17.99 A Political Theology of Nature, Peter Scott, Cambridge University Press 2003 (Hb 0-521-64165-9, Pb 0-521-52717-1), pp. xiii + 275, Hb £47.50, Pb £17.95 Re-ordering Nature: Theology, Society and the New Genetics, Celia Deane-Drummond, Bronislaw Szerszynski and Robin Grove-White (eds), T. & T. Clark 2003, A Continuum Imprint (Hb 0-567-08896-0, Pb 0-567-08878-2), pp. xiv + 368, Hb £50, Pb £17.99 Subverting Greed: Religious Perspectives on the Global Economy, Paul F. Knitter and Chandra Muzaffar (eds), Orbis Books 2002 (1-57075-446-2), pp. xiv + 193, Pb $20 Marriage and Modernization: How Globalization Threatens Marriage and What To Do About It, Don S. Browning, Eerdmans 2003 (0-8028-1112-4), pp. xiv + 292, Pb £21.99/$30 Spiritual Caregiving as Secular Sacrament: A Practical Theology for Professional Caregivers, Ray S. Anderson, Jessica Kingsley Publishers 2003 (1-84310-746-5), pp. 192, Pb £15.95/$24.95 Growing Old in Christ, Stanley Hauerwas, Carole Bailey Stoneking, Keith G. Meador, and David Cloutier (eds), Eerdmans 2003 (0-8028-4607-6), pp. x + 310, Pb £17.99/$24 Psychotherapy and Spirituality, Agneta Schreurs, Jessica Kingsley Publishers 2002 (1-85302-975-0), pp. 313, Pb £17.95/$26.95 Islam and the West: Conflict or Cooperation?, Amin Saikal, Palgrave Macmillan 2003 (1-4039-0358-1), pp. x + 171, Pb £13.99 Gender, Politics, and Islam, Therese Saliba, Carolyn Allen, and Judith A. Howard (eds), University of Chicago Press 2002 (0-226-73428-5), pp. 354, Hb $39 Searching for God in Godforsaken Times and Places: Reflections on the Holocaust, Racism, and Death, Hubert G. Locke, Eerdmans 2003 (0-8028-6084-2), pp. x + 109, Pb £12.99/$18